(untitled) (Praxis Educativa, 2023)
This article develops the School Retention Program for Mothers and Pregnant Students beginnings that has been operating in the City of Buenos Aires (Argentina) since 1999. Following a qualitative approach and on the basis of case studies, we problematize the Program origins asan oriented policy in the Buenos Aires southern area and analyze the pedagogical devices created to guarantee the educational continuity of this particular population.